Crossing language boundaries. The use of English in advertisements in Polish lifestyle magazines - Marta Dąbrowska (LingBaW)
Advertising is an area open to various types of innovation and a creative use of language. Advertisers use a variety of strategies to attract as many customers as possible, employing enticing visuals, clever puns, detailed descriptions, direct appeals, etc. Yet, if the product is to sell, it appears self-evident that the language of the advertisement should not constitute a barrier. Contrary to this assumption, however, there has been an ever growing trend visible in Polish magazines for the last two decades to formulate parts of or even complete advertisements, not infrequently of Polish brands, in English, despite the fact that English remains a foreign language in Poland, although, admittedly, a very popular one.